Jump ship to freedom - Collier, James L. (Delacorte Press, 1981)
In 1787 a fourteen-year-old slave, anxious to buy freedom for himself and his mother, escapes from his dishonest master and tries to find help in cashing the solidier's notes received by his father for fighting in the Revolution.